The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fmicb.2018.02719
|View full text |Cite
|
Sign up to set email alerts
|

Role of Temperate Bacteriophage ϕ20617 on Streptococcus thermophilus DSM 20617T Autolysis and Biology

Abstract: Streptococcus thermophilus DSM 20167T showed autolytic behavior when cultured in lactose- and sucrose-limited conditions. The amount of cell lysis induced was inversely related to the energetic status of the cells, as demonstrated by exposing cells to membrane-uncoupling and glycolysis inhibitors. Genome sequence analysis of strain DSM 20617T revealed the presence of a pac-type temperate bacteriophage, designated Φ20617, whose genomic organization and structure resemble those of temperate streptococcal bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
(74 reference statements)
3
10
0
Order By: Relevance
“…Autolysis was triggered under unfavorable environmental conditions (Soda et al, 1995). Although autolysis is not a common phenomenum in S. thermophilus (Arioli et al, 2018), the autolytic behavior occurred under lactose limitation (Thomas and Crow, 1983), consistent with the present results. The translational levels of muramidase, endopeptidase, and N-acetyl-muramoyl-L-alanine amidase, which promotes peptidoglycan autolysis, increased significantly during the late-exponential phase in S. thermophilus (Qiao et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Autolysis was triggered under unfavorable environmental conditions (Soda et al, 1995). Although autolysis is not a common phenomenum in S. thermophilus (Arioli et al, 2018), the autolytic behavior occurred under lactose limitation (Thomas and Crow, 1983), consistent with the present results. The translational levels of muramidase, endopeptidase, and N-acetyl-muramoyl-L-alanine amidase, which promotes peptidoglycan autolysis, increased significantly during the late-exponential phase in S. thermophilus (Qiao et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…In strains APC151 and ND03 the same prophage was predicted located within the EPS cluster of each strain. In strain NCTC12958 T the intact prophage was previously described as phage 20617 by Arioli et al (2018). Interestingly, the authors of this study demonstrated that the lysogenic strain NCTC12958 T (DSM 20617 T ) exhibited higher adhesion to solid surfaces and heat resistance compared to the phage-cured derivative strain, suggesting some competitive advantage due to the stable association of the phage and the host.…”
Section: R-m Systems and Prophagesmentioning
confidence: 75%
“…Downstream to the left host-phage junction ( att L), bacterial genes encoding enolase, glycogen synthase, and glycerate kinase were found, while upstream to the right junction ( att R), bacterial genes encoding isoleucyl-tRNA synthetase, lipoteichoic acid synthase, methyltransferase, and 3-dehydroquinate dehydratase were identified. These integration sites have high similarity with those identified in the temperate bacteriophage Φ20617 [37], as revealed by the nucleotide BLAST analysis that showed 84% of identity between both viruses and a query cover of 76%. Presence of the tRNA synthetase genes in the att sites is a common feature, since tRNA coding regions have been recognized as integration site “hotspots” for viruses [54].…”
Section: Resultsmentioning
confidence: 68%
“…Unrooted phylogenetic tree was computed, using the SplitsTree4 following the neighbor joining method [35]. A whole genome comparison with pac -type phages from the genus Sfi11virus, TP1-M17PTZA496, and Streptococcus phage 20617, was performed, using the Easyfig comparison tool [36,37,38]. Finally, CRISPRdb [39] and HostPhinder [40] tools were used to predict the potential bacterial hosts of the identified prophages.…”
Section: Methodsmentioning
confidence: 99%